ANALISIS KESALAHAN BERBAHASA INDONESIA PADA KOMUNIKASI ILMIAH FISIKA - Auji Khalizah; Diana Elfrida Marpaung; Nia Cristina Simalango; Veronika Tumanggor; Nurul Azizah (STKIP Subang, 2026)
This study aims to analyze various forms of Indonesian language errors found in scientific communication in physics. The research employed a qualitative descriptive method using a literature study approach. Data were collected from journals, scientific articles, and physics teaching materials discussing the use of Indonesian in academic writing. Data collection techniques included documentation and literature review, while data analysis was conducted through identifying, classifying, and describing the language errors found in the sources. The findings indicate that language errors are still frequently encountered in scientific communication in physics, particularly in spelling, capitalization, punctuation, word choice, and ineffective sentence structures. These errors may reduce the clarity of information, lower the quality of scientific writing, and lead to misunderstandings of physics concepts presented in the text. Furthermore, limited understanding of Indonesian language rules and inadequate editing processes were identified as factors contributing to language errors. Therefore, improving the proper use of Indonesian language according to linguistic standards is necessary to support effective, accurate, and comprehensible scientific communication in physics.